Using RAPD-PCR as molecular assessment on the performance of CHROMAgar™ Listeria and PALCAM agar on isolation of Listeria spp. and L. monocytogenes from foods - Lee, Hai Yen; Chai, Lay Ching; Pui, Chai Fung; Robin, Tunung; Wong, Woan Chwen; Mustafa, Shuhaimi; Cheah, Yoke Kqueen; Mohamad Ghazali, Farinazleen; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
In this study, Listeria spp. were isolated from naturally contaminated samples of beef burger, minced beef and sliced cheese using PALCAM and CHROMagar™. Samples were enriched with FDA-BAM method and plated on PALCAM and CHROMagar™ Listeria before confirmation using PCR on hlyA and LLO toxin genes specific to L. monocytogenes. Identification of isolates showed a total of 45 isolates of Listeria spp. and two L. monocytogenes. All the 47 isolates were then subjected to RAPD analysis using two oligomers (OPA14 and OPA15) and fingerprint clustering was able to cluster the L. monocytogenes from Listeria spp. based on isolation from agar types as well as L. monocytogenes from Listeria spp. Studies showed that OPA14 and OPA15 are useful for rapid discrimination of Listeria spp. and L. monocytogenes . The differences observed on the isolation of Listeria spp. from PALCAM and CHROMagar™ Listeria that may have an impact on epidemiological studies.